PENGARUH KEHADIRAN MODERN MARKET LEMBANG DAN DAMPAKNYA TERHADAP DINAMIKA PASAR TRADISIONAL: PERSPEKTIF DARI PERSEPSI MASYARAKAT - Sulaeman, Fitriani (International Journal Administration, Business & Organization, 2025)
Modern markets in various regions often create challenges for traditional markets, including in the Lembang area. This study aims to examine the influence of Modern Market Lembang on the dynamics of traditional markets. Using a quantitative approach supported by a structured survey distributed to local residents and market participants, this study found that Modern Market Lembang exerts a moderate influence on the sustainability of traditional markets. Although modern markets are preferred for their convenience, product quality, standardized pricing, and attractive promotional strategies, traditional markets continue to hold significance within the community due to their warm social interactions, price flexibility, personalized service, and strong consumer loyalty. Furthermore, the research identifies key factors influencing consumer behavior shifts, including perceived value, accessibility, and cultural attachment to traditional shopping experiences. The findings suggest that rather than being purely competitive, modern and traditional markets have the potential to complement each other by offering diversified shopping experiences that cater to different consumer needs. Strategic initiatives such as service innovation, infrastructure improvement, and collaborative promotional efforts are critical for enhancing the competitiveness of traditional markets. In conclusion, strengthening the synergy between modern and traditional markets is essential for ensuring balanced market dynamics, preserving local cultural identity, and fostering sustainable economic growth in the Lembang region.